Integration of diagnosis and treatment of sleeping sickness in primary healthcare facilities in the Democratic Republic of the Congo. Issue 1 (20th October 2014) - Mitashi, P.; Hasker, E.; Mbo, F.; Van Geertruyden, J.P.; Kaswa, M.; Lumbala, C.; Boelaert, M.; Lutumba, P.
Abstract Background Control of human African trypanosomiasis (HAT) in the Democratic Republic of Congo (DRC) has always been a vertical programme, although attempts at integration in general health services were made in recent years. Now that HAT prevalence is declining, the integration question becomes even more crucial. We studied the level of attainment of integration of HAT case detection and management in primary care centres in two high‐prevalence districts in the province of Bandundu, DRC. Methods We visited all 43 first‐line health centres of Mushie and Kwamouth districts, conducted structured interviews and inspected facilities using a standardised checklist. We focused on: availability of well trained staff – besides HAT, we also tested for knowledge on tuberculosis; availability of equipment, consumables and supplies; and utilisation of the services. Results All health centres were operating but most were poorly equipped, and attendance rates were very low. We observed a median of 14 outpatient consultations per facility (IQR 8–21) in the week prior to our visit, that is two patients per day. The staff had good knowledge on presenting symptoms, diagnosis and treatment of both HAT and tuberculosis. Nine centres were accredited by the national programme as HAT diagnosis and treatment centres, but the most sensitive diagnostic confirmation test, the mini‐anion exchange centrifugation technique (mAECT), was not present in any. Although all nine were performing the CATT screening test, only two had the required cold chain in working order. Conclusion In these high‐prevalence districts in DRC, staff is well‐acquainted with HAT but lack the tools required for an adequate diagnostic procedure. Attendance rates of these primary care centres are extremely low, making timely recognition of a resurgence of HAT unlikely in the current state of affairs.